Reconciling Economic and Environmental Imperatives in Batam. - Onn, Lee Poh (ISEAS - Yusof Ishak Institute, 2018)
Batam's economic transformation has been accompanied by a marked degradation of its natural environment. Enforcement to protect the environment has often been inadequate on many fronts, exacerbated by population increases. Though regulations exist for the provision of public amenities like wastewater and sewerage treatment, existing facilities are run-down and ill-equipped to cope with the present demands. The capacity of reservoirs to meet the present demand for water is also strained because of the large population base, with illegal intrusion and squatters further threatening supplies. Economi.